(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
This study aims to explore the opportunities and challenges of ensuring Algeria’s transition from successful traditional sovereignty to guaranteeing digital sovereignty, using scientific indexes and the experience of China as a global model in the era of digital transformation. To achieve this, we adopted an analytical methodology focused on several global indicators related to digital transformation over the past eight years (2017-2024). These include the Global Knowledge Index, the Global Innovation Index, and the Artificial Intelligence Index. In addition to these digital inputs, our study also incorporated economic and legislative inputs, such as gross domestic product (GDP), the percentage of GDP spending on research and development, and legislative policies. Given Algeria’s ambition to position itself as an emerging knowledge-based economy, we have drawn on evidence from China as a successful global model. The results of the study found that Algeria has the necessary capabilities that enable it to enhance its digital, economic and legislative inputs, and that the criterion for its success in ensuring digital sovereignty is reflected by improving its global ranking in global indicators related to digital transformation, especially infrastructure, research and development, advertising and communication technologies, digital environment, and legislative policy. Keywords: Digital Sovereignty, Knowledge, Innovation, AI, Algeria